Agricultural Producer Attitudes Toward Agri-Tourism in Miami-Dade County, Florida - Thomas J. Stevens; Robert L. Degner; Kimberly L. Morgan (EDIS)
This is EDIS document FE359, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published October 2002.